Alvarado vs. Pediatric Appendicitis Score (PAS) in Acute Appendicitis of Children - Davoud Badebarin; Sina Parsay; Saeed Aslanabadi (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Acute appendicitis in children is associated with morbidity and mortality due to late diagnosis. Several scoring systems, such as Alvarado and PAS have been developed to help diagnose acute appendicitis in children to make the most accurate and prompt decision. The purpose of this study was to compare the efficacy and diagnostic value of these scoring systems. Materials and Methods: In this cross-sectional study, 130 children aged 5-14 with suspected acute appendicitis were included. After the collection of demographic data, all patients were scored by Alvarado and PAS systems. The decision for surgery was made by a surgeon, independently of these scores. The diagnosis of acute appendicitis was affirmed by surgical and pathologic findings. Results: Male: Female ratio was 1.32:1, and the average age of the patients were 9.2±2.7 years. The mean Alvarado and PAS scores were higher in patients with positive pathologic findings. Neutrophilia >75% and RLQ tenderness had the highest relationship with the diagnosis of the disease. The diagnostic value of Alvarado was higher than PAS concerning the area under the ROC curve. The cutoff point of 7 was associated with a sensitivity of 74.5% and specificity of 66.7% for the Alvarado score, and a sensitivity of 58.5% and specificity of 79.2% for the PAS score. Conclusions: The results showed the high sensitivity of Alvarado and the high specificity of PAS. However, the sensitivity, specificity, PPV, and NPV of these criteria were not satisfactory for the confirmation of the diagnosis.